Neuropeptide GPCRs in C. elegans - Frooninckx, Lotte; Van Rompay, Liesbeth; Temmerman, Liesbet; Van Sinay, Elien; Beets, Isabel; Janssen, Tom; Husson, Steven J.; Schoofs, Liliane (Frontiers in Endocrinology, 2012)
Like most organisms, the nematode Caenorhabditis elegans relies heavily on neuropeptidergic signaling. This tiny animal represents a suitable model system to study neuropeptidergic signaling networks with single cell resolution due to the availability of powerful molecular and genetic tools. The availability of the worm’s complete genome sequence allows researchers to browse through it, uncovering putative neuropeptides and their cognate G protein-coupled receptors (GPCRs). Many predictions have been made about the number of C. elegans neuropeptide GPCRs. In this review, we report the state of the art of both verified as well as predicted C. elegans neuropeptide GPCRs. The predicted neuropeptide GPCRs are incorporated into the receptor classification system based on their resemblance to orthologous GPCRs in insects and vertebrates. Appointing the natural ligand(s) to each predicted neuropeptide GPCR (receptor deorphanization) is a crucial step during characterization. The development of deorphanization strategies resulted in a significant increase in the knowledge of neuropeptidergic signaling in C. elegans. Complementary localization and functional studies demonstrate that neuropeptides and their GPCRs represent a rich potential source of behavioral variability in C. elegans. Here, we review all neuropeptidergic signaling pathways that so far have been functionally characterized in the worm.